If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying -1 + 10 = 3b + -5 + -2b Combine like terms: -1 + 10 = 9 9 = 3b + -5 + -2b Reorder the terms: 9 = -5 + 3b + -2b Combine like terms: 3b + -2b = 1b 9 = -5 + 1b Solving 9 = -5 + 1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 9 + -1b = -5 + 1b + -1b Combine like terms: 1b + -1b = 0 9 + -1b = -5 + 0 9 + -1b = -5 Add '-9' to each side of the equation. 9 + -9 + -1b = -5 + -9 Combine like terms: 9 + -9 = 0 0 + -1b = -5 + -9 -1b = -5 + -9 Combine like terms: -5 + -9 = -14 -1b = -14 Divide each side by '-1'. b = 14 Simplifying b = 14

| 3x^2-7x+12=1 | | x-3=23 | | x+0.05x=126 | | (x^2)+2x-48=0 | | 8(3t+2)-60=28 | | 3y-6x=12 | | 6x+9=5x-7 | | 4(2f-3)+3=39 | | x^2+14-12=0 | | 6(2x-7)-6=6(x-2)+6 | | 7(2n+3)=91 | | (x^2)+x-110=0 | | 6(s-7)=3(4s+4) | | 7x-4x=16+5x | | (x^2)-18x+77=0 | | 7-4x=16+5x | | x=4+4y | | x=4y+4 | | (x^2)-6x-7=0 | | (x+6)(x+2)= | | 9x^2+6x-35=0 | | x^2+3x=7 | | 5(3y+2)+10=105 | | (x^2)+7x=-12 | | (x-5)(x-4)= | | (a+7)(a+2)= | | y+x=z | | x+y=zy | | (x^2)+6x=40 | | (b-8)(b+5)= | | 4(x+7)=8x+4-4x+24 | | (c+4)(c-6)= | | (d-3)(d-10)= | | 6=.16z+8 | | 6-2x=4x-7 | | 3x^2+2x-7=0 | | h=-16t^2+676 | | 2m(b+5)+m(b+5)= | | 11(x+1)-4(x-1)=2(x-3)+4(x-3) | | (a+3)x-(a+3)y= | | 2y+2(y-2)=5y-3(y-10) | | 5x^2+20x+10=0 | | 9x-2=9(x+5) | | 27+b=18 | | 9=.2z+12 | | 2x+1=-71 | | 3x=-8+66 | | 3x=8x+66 | | 25b^2+80b+64=0 | | y=3x^2+12x-8 | | 5x+20x+10=0 | | 5+7t=23+t | | 12x-15y=120 | | 4(-8+x)=5x+0.5 | | 3c-1=-4 | | 10=.2a+2 | | x^2-8+10=0 | | ((x+11)+24)x=1752 | | 5(2X-5)-3=21 | | (5+x)-4=106 | | 27=15+5x-6 | | x=25+25x+x^2+x^3 | | 5(2X-5)-3=12 | | -5x+54=-36 | | 16x-14x=6 |